Равнопрочная форма отверстия для торможения роста трещины продольного сдвига - Калантарлы, Н.М. (Проблемы машиностроения, 2017)
Рассмотрена задача об отыскании равнопрочной формы отверстия в кончике трещины и ее влияния на развитие трещины. Предложен критерий и метод решения задачи по предотвращению хрупкого разрушения тела, ослабленного трещиной продольного сдвига. Получено условие хрупкого разрушения. Розглянуто задачу про відшукування рівноміцної форми отвору в кінчику тріщини та її вплив на розвиток тіщини. Запропоновано критерій та метод розв’язування задачі з запобігання крихкому руйнуванню тіла, ослабленого тріщиною поздовжнього зсуву. Отримано умову крихкого руйнування. The problem of finding an equistrong hole shape in crack tip and its effect on crack development is considered. A criterion and method for the problem solution to prevent brittle fracture of solid weakened by longitudinal shear crack is proposed. Using the perturbation method and the conformal mapping to parametric plane, the problem in each approximation is reduced to boundary value problem for analytic function. In each approximation, the solution of the boundary value problem for analytic function in the class of everywhere bounded functions (stresses) is obtained in closed form. The reduction of the stress concentration on the hole’s contour in the crack tip is done by the method of least squares. To determine expansion coefficients of the Fourier series of the required hole shape function and the optimal value of circumferential tangential stress in surface layer of the hole an infinite linear system of algebraic equations is obtained for elastic material. The condition of brittle fracture is obtained.